2011
DOI: 10.5194/se-2-9-2011
|View full text |Cite
|
Sign up to set email alerts
|

Reflection seismic studies over the end-glacial Burträsk fault, Skellefteå, Sweden

Abstract: Abstract. Reflection seismic data were acquired along a ca. 22 km long profile over the end-glacial Burträsk fault with a nominal receiver and source spacing of 20 m. A steeply dipping reflection can be correlated to the Burträsk fault, indicating that the fault dips at about 55 • to the southeast near the surface. The reflection from the fault is rather poorly imaged, probably due to a lateral offset in the fault of about 1 km at this location and the crookedness of the seismic profile in the vicinity of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Computational geophysics is essential to study the structure of the earth on the basis of seismic forward modeling, inversion and interpretation (Zappone, 1994;Long and Silver, 2009;Juhlin and Lund, 2011). In particular, grid methods are required for simulating wave propagation in heterogeneous realistic models (e.g., Carcione et al, 2002;Seriani et al, 1992).…”
mentioning
confidence: 99%
“…Computational geophysics is essential to study the structure of the earth on the basis of seismic forward modeling, inversion and interpretation (Zappone, 1994;Long and Silver, 2009;Juhlin and Lund, 2011). In particular, grid methods are required for simulating wave propagation in heterogeneous realistic models (e.g., Carcione et al, 2002;Seriani et al, 1992).…”
mentioning
confidence: 99%
“…No outcrops of basement rocks are found in the vicinity of the scarp, hence no fault or fault plane and sense of movement can be directly associated with the scarp. However, most glacially induced faults appear to be dominantly reverse, dipping between 50 and 60 • (Juhlin et al, 2010;Juhlin and Lund, 2011;Ahmadi et al, 2015) and associated with zones of weakness in the bedrock (e.g. shear zones or at rock contacts).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…1). Based on the results from a reflection seismic survey, Ahmadi et al (2015) reported on the Pärvie post-glacial fault in Sweden, which they imaged down to about 8 km depth (see also Juhlin et al, 2010;Juhlin and Lund, 2011;Lindblom et al, 2015). To the best of our knowledge all known post-glacial faults have been reported to be associated with pre-existing structures (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The length of the PGFs may vary from 2 to 150 km and the maximum height of the fault scarps from 1 to 12 m, and up to 30 m in the extreme cases (see compilation in Olesen et al, 2004). However, postglacial faulting is not confined to northern Fennoscandia, but has also been reported in northernmost Germany (Brandes et al, 2012) and central parts of Sweden and Finland (Malehmir et al, 2016;Mikko et al, 2015;Palmu et al, 2015;Juhlin and Lund, 2011;Juhlin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%